“Intelligent and Autonomous. Transforming Values in the Face of Technology”.: A review of the book edited by I. Kalpokas and J. Kalpokene - Boychenko, Nataliia (Filosofiya osvity. Philosophy of Education, 2025)
The book “Intelligent and Autonomous: Transformation of Values in the Face of Technology”, edited by Ignas Kalpokas and Julija Kalpokienė (Vytautas Magnus University, Lithuania), is a profound study of the changes brought about by technological progress, particularly the development of the application of artificial intelligence in the field of values, morality, and social norms. The authors analyze how autonomous AI-based systems challenge traditional notions of human agency, responsibility, and freedom while also proposing possible approaches to regulating their use. The authors emphasize that technologies not only influence our daily lives but also shape new conditions for societal existence, creating a need for the development of appropriate moral judgments and ethical imperatives. Overall, the book offers not only an in-depth analysis of contemporary challenges but also outlines potential approaches to technology regulation to preserve fundamental human values.